The strange case of Dr. Jekyll and Mr. Hyde - Stevensen, Robert Louis, 1850-1894 ([Boston, Mass] : Thomson Heinle, 2005)
The story of respectable Dr. Jekyll's strange association with'damnable young man' Edward Hyde, the hunt through fog-bound London for a killer, and the final revelation of Hyde's true identity is a chilling exploration of humanity's basest capacity for evil
Title from container
Keywords: Horror tales, English; Physicians -- Fiction; Multiple personality -- Fiction; Self-experimentation in medicine -- Fiction; London (England) -- Fiction